Analysis of a Blended, In-Service, Continuing Education Course in a Public Health System: Lessons for Education Providers and Healthcare Managers - Manzini, Fernanda; Diehl, Eliana Elisabeth; Farias, Mareni Rocha; dos Santos, Rosana Isabel; Soares, Luciano; Rech, Norberto; Lorenzoni, Andrigo Antonio; Leite, Silvana Nair (Frontiers in Public Health, 2020)
Introduction: To train pharmacists working in the public health system, the Brazilian Ministry of Health developed a specialization course called Pharmaceutical Service and Access to Medicine Management (PSAMM) between 2010 and 2016. The course was free of charge and used e-learning as its main approach. In the end, 2,500 pharmacists were trained. The purpose of this study was to identify and analyze the strengths, weaknesses, opportunities, and threats of an in-service and e-learning course for pharmacists working in a public health system. Materials and Methods: Three workshops involving 67 participants were conducted at the conclusion of the course to analyze the perspective of the PSAMM course's faculty (tutors, regional coordinators, professors, and management committee) and students (pharmacists). Strengths, weaknesses, opportunities, and threats analysis and qualitative analysis methods were used. Results and Discussion: The strength dimension had the greatest number of items. The qualitative analysis resulted in six categories: the category “E-learning in continuing education” had the most cited items. Internal elements such as in-service hands-on activities directly related to the professionals' roles, course contents, faculty, and the methods to offer the course (the mixed methods and materials) were positively assessed. Nonetheless, external elements were considered critical for the course's outcomes such as investments in the infrastructure of pharmaceutical services, access to the internet, local managers' support for continuing education and innovation implementation, practice of interprofessional collaboration, and political stability. The continuing education course in the public health system was affected by internal elements such as its project and structure as well as external elements such as the sociopolitical scenario. Continuing education investment must be accompanied by infrastructure investment and coordination of services.